Coir Fibre Sourced Projects: Elevated Adinkra Wall Hangings - Richard Acquaye; Deborah Kusi Appiah; Adelaide Oboshie Sai (Fashion and Textiles Review)
This project extracted coconut fibres via low technology processes and converted the fibres into useful hand-made functional Adinkra themed wall hangings. Some of the major properties (chemical and physical) and application of the coir fibres are utilised and discussed in the process. The Adinkra wall hangings include symbols such as Anansi Ntontan, Boa Me Na Me Mmoa Wo, Gye Nyame, Mate Masie, Nkyinkyim and Nsaa. This project is one of many that is seeking to address the problem of managing coconut husk and for that matter other natural by-products and waste in Ghana. Coconuts abound from the coast through the forest regions to the middle belt of the country. Coconut juice sellers and coconut oil producers are known for dumping coconut shells and husks at unauthorized places after close of business or production each day. Even though coconut husks are biodegradable, if not properly disposed they contribute to the waste problem in many prime areas in Ghana. This is so because solid waste management in Ghana is a huge challenge affecting the lives of every ordinary person of the country as well as the environment. This project conjectures that there is a huge economic potential of coconut and its waste products which has remained largely untapped in Ghana. The potential of the coconut crop has been grossly under-utilized in Ghana, hence there is the need to research and explore the many potentials of coconut fibres that includes utilitarian products. In this study, coir fibres are mixed with glue as binders to produce elevated wall hangings for decoration.